2020
DOI: 10.1177/0164027520922624
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering, Subjective Sleep Quality, and Chronic Inflammation: A 5-Year Follow-Up of the National Social Life, Health, and Aging Project

Abstract: Studies indicate that the benefits of volunteering may extend to biological risk factors in disease development including chronic inflammation, though the pathway through which volunteer activity predicts chronic inflammation remains unclear. The current project focuses on the link between volunteering and C-reactive protein (CRP) as a measure of chronic inflammation, while paying a particular attention to sleep quality as a pathway. Using panel data from the National Social Life, Health, and Aging Project ( N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Second, inflammation is a key factor strongly associated with depression. The study reported that short sleep duration and insomnia symptoms were associated with increases in inflammatory cytokines such as CRP and IL6 [ 40 , 41 ]. Third, good sleep helps boost levels of melatonin [ 42 ], a molecule that regulates pleiotropic effects that reduce symptoms of depression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, inflammation is a key factor strongly associated with depression. The study reported that short sleep duration and insomnia symptoms were associated with increases in inflammatory cytokines such as CRP and IL6 [ 40 , 41 ]. Third, good sleep helps boost levels of melatonin [ 42 ], a molecule that regulates pleiotropic effects that reduce symptoms of depression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, a major explanation is inflammation, a key factor strongly associated with depression [ 33 ]. Studies have reported both short and long sleep durations and poor sleep quality to be associated with increased inflammatory cytokines such as CRP and IL6 [ 34 36 ]. Second, good sleep quality could help increase levels of melatonin [ 37 ], a pleiotropic regulator molecule that has been reported to alleviate depressive symptoms [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that poor sleep quality may lead to a series of changes in hormonal, metabolic, and inflammatory status of the people. For example, insomnia has been related with insulin resistance, activated inflammatory response, and enhanced systematic oxidative stress (Hashemipour, Ghorbani, Khashayar, & Olfati, 2021 ; Irwin & Vitiello, 2019 ; Kim & Yoon, 2020 ), all of which may lead to protein synthesis impairment and sarcopenia, a major cause of physical frailty in the older (Cleasby, Jamieson, & Atherton, 2016 ; Umegaki, 2016 ). Studies are needed for further clarification of the mechanisms.…”
Section: Discussionmentioning
confidence: 99%